Implementasi Teologi Pembebasan dalam Pendidikan: Peran YES Academy dalam Pengajaran Bahasa Inggris bagi Anak-anak Desa Aek Raja - Tiffany Brame; Frenty Sariyati; Rencan Carisma Marbun (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This research aims to analyze the implementation of Liberation Theology principles in free education services provided by YES Academy (YA) in Aek Raja Village, Parmonangan District, North Tapanuli Regency. The main problem identified was parents' economic limitations which resulted in village children not being able to attend additional education outside of school, so that their English skills lagged behind those of students from urban areas. YA exists as a real form of faith practice by providing free English education for around 85 students, served by a team of 7 teachers. The research methodology uses a descriptive qualitative approach with case studies, through interviews, observations and documentation studies. The research results show that YA not only improves students' academic abilities, but also becomes a means of communication and social empowerment for village residents. The discussion emphasized that YA's steps are in line with the principle of preferential option for the poor in Liberation Theology, where education is seen as an instrument of social transformation that is able to reduce structural injustice and bring justice to marginalized groups. This research concludes that YA functions as a liberating agent that lives out the prophetic spirit of the church, while providing a contextual educational model that is relevant to village communities.